Microbacterium spp. peritonitis in patients undergoing peritoneal dialysis: a single-center experience and literature review - Yu, Xiao; Li, Zhao; Yang, Xinbo; Wang, Xiaopei; Nan, Di; Lu, Wanhong; Lv, Jing; Ma, Ying (Frontiers in Medicine, 2023)
INTRODUCTION: Peritoneal dialysis-related peritonitis (PDRP) caused by Microbacterium spp. is very rare, with only 9 cases reported to date. In this study, we report the treatment experiences of 7 patients at our peritoneal dialysis center. METHODS: We retrospectively collected clinical characteristics and antibiotic management of all 7 episodes of PDRP caused by Microbacterium spp. in 7 patients from at our center over 4 years, and reviewed the documented Microbacterium spp. PDRP in the literature. RESULTS: Empiric antibiotic therapy was initiated as soon as possible, and consisted of intraperitoneal (IP) gentamicin in combination with vancomycin. After up to 5 days, gentamicin was changed to meropenem if the treatment was not effective. The intended course of antibiotic treatment was 21-day. Totally, 6 episodes were cured (85.7%), which was higher than reported. CONCLUSION: The 21-day antibiotic therapy program by combining vancomycin and meropenem may benefit the management of Microbacterium spp. PDRP.